Interventions to improve referrals from primary care to outpatient specialist services for chronic conditions: a systematic review and framework synthesis update - Layla Bolton Saghdaoui; Smaragda Lampridou; Sara Tavares; Rachael Lear; Alun Huw Davies; Mary Wells; Sarah Onida (Systematic Reviews)
Abstract Background Prior systematic reviews highlight that accessing specialist healthcare to treat chronic conditions can be obstructed by variations in referral rates, inappropriate referrals, and poor communication. Structured referral proformas, peer feedback, and educational interventions involving specialists have been identified as successful strategies for improving referral rates and appropriateness. However, the success of such interventions is often dependent on specific clinical contexts, and little is known about the practicalities of implementation. Additionally, with advancements in healthcare delivery, such as e-referral systems, there is a need to explore new interventions and how they address barriers to referral. Methods This systematic review evaluated the updated evidence exploring interventions aiming to improve rates and/or appropriateness of referral from primary care to specialist services in patients with chronic conditions.Five academic databases were searched (CINAHL, MEDLINE, Embase, British Nursing Index, and Public Health Database), and studies published in English between 2013 and 2023 were included. The Joanna Briggs Institute’s appraisal tool was used to assess the quality of studies, and a narrative synthesis was conducted using the TiDiER framework (template for intervention description and replication). Results Eighteen full-text publications and five abstracts were included. A behavioral theory or framework for intervention development was used in seven studies. All interventions were based on primary care, and thirteen studies evaluated a multi-component intervention. Process and system changes were most commonly used to improve referral, including electronic health systems, referral algorithms, collaborative working, and patient direct access. Interventions targeted at patients were the least common. Staff education was often used in addition to process and system changes. When used alone, referral algorithms and staff education were less effective at improving referral rates or appropriateness. Implementation barriers included time constraints, logistical issues, and patients/staff preconceived perceptions of referral necessity. Conclusion Unsurprisingly, the success of interventions aimed at improving referral practices is based on contextual circumstances, and as with previous reviews, there is no one-size-fits-all approach.Given the challenges highlighted in this review, multi-component interventions addressing referral barriers in both primary and secondary care appear to be a successful way to improve referral practices. Review registration PROSPERO CRD42023480493